Pengaruh Kelompok Belajar Terhadap Kinerja Mahasiswa Teknologi Pendidikan UPI - ., Azkia Aulia Rahma; ., Fahdi Nur Fauzi; ., Nur Anisa Fitri; ., Rizvan Akmal Wirawan; ., Wahyu Imam Rajani (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
Study groups are a group of individuals who come together to share knowledge and discuss certain topics and they usually have the same goal. This study aims to determine the effect of study groups on the performance of Educational Technology students at the Indonesian University of Education. The method used in this study is a quantitative method by distributing questionnaires containing several statements about study groups in which the subjects are Educational Technology students at the Indonesian University of Education. The results of this study indicate that study groups have a positive impact on the performance of Educational Technology students at the Indonesian University of Education which increases understanding, social skills, and provides encouragement and motivation for them to achieve success together.